Homeland Security: Establishment and Implementation of Northern Command - Bolkcom, Christopher; DeSerisy, Lloyd; Kapp, Lawrence (Library of Congress. Congressional Research Service., 2002)
Report on the Defense Department's (DoD) establishment of U.S. Northern Command (NORTHCOM) advancements towardsfighting terrorism, as well as issues relating to NORTHCOM's relationships with other agencies within the DoD.